2020
DOI: 10.3390/w12010151
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rainwater Management Concept in a Housing Estate with a Financial Feasibility Assessment and Motivational Rainwater Fee System Efficiency Analysis

Abstract: Unresourceful usage of rainwater continues to be a serious problem as this type of natural resource is still treated as wastewater that most often ends up directly in the sewer system. The aim of the article is to present a concept of sustainable rainwater management within a completed housing estate in Cracow (Poland). Sustainable solutions are proposed, such as rain gardens, soakaways, permeable surfaces, and infiltration boxes, limiting the surface runoff, feasible for implementation in an existing developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
0
19
0
2
Order By: Relevance
“…The rational method of runoff calculation is based on rainfall intensity in the form of [60,[97][98][99]:…”
Section: Runoff Estimation As An Assessment Of Water Cycle Disturbancementioning
confidence: 99%
See 3 more Smart Citations
“…The rational method of runoff calculation is based on rainfall intensity in the form of [60,[97][98][99]:…”
Section: Runoff Estimation As An Assessment Of Water Cycle Disturbancementioning
confidence: 99%
“…Stormwater fees are common in the U.S. and Canada, as shown by the latest survey from 2021 [55]. Research on stormwater fees has been the subject of many analyses of their impact on the development of green infrastructure, which proved their effectiveness; for example: (1) the assessment of stormwater fees in Germany (also noted as imperviousness fees) [56][57][58] showed a 10% decrease in the impervious area in Munich [56]; (2) Qiao et al, in two research papers [17,45], analyzed the governance factors of sustainable stormwater management and recommended the use of stormwater fees as an important incentive; and (3) analyses of stormwater fees in Poland were conducted in terms of their impact on the economic efficiency of green infrastructure [59][60][61], and they were also mentioned as important factors in the development of sustainable stormwater management [62,63]. Thurston et al analyzed auctions and fees as incentive methods, and concluded that relatively minimal financial incentives could encourage homeowners to retain stormwater runoff on their property [47].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Godyń et al [10] discuss different rainwater management strategies for the retrofitting of housing estates. In Poland, investments in Green Infrastructure are still not common practice.…”
Section: Policy Regulations and Financial Aspectsmentioning
confidence: 99%